The Diffusion and Social Implications of MOOCs A Comparative Study of the USA and Europe - Goglio, Valentina (Taylor & Francis, 2022)
Based on new empirical research, including qualitative interviews as well as quantitative data from learners across several MOOCs, this book contributes to the debate by providing a comparative study of the diffusion and social implications of MOOCs in the USA and in Europe.